Managing change in modern organizations: key issues and possible solutions - O. V. Divnenko; D. A. Gorsky (Informaciâ i Innovacii, 2020)
The article discusses major issues in managing change processes in the organizations. The specific reasons for the setbacks in the implementation of organizational change are being addressed.